Role of Biochar in heavy metal remediation - Dotaniya, M L; Meena, M D; Doutaniya, R K; Meena, V D; Dotaniya, C K; Meena, L K; Choudhary, R L (Indian Farming, 2022)
Natural resource health is deteriorating at an alarming rate and it is estimated that by 2050, India will require 333 million tonnes of food grain to feed the growing population. Therefore, it’s time to make better use of natural resources and clean up the contaminated agricultural land before planting crops. Pollutants of many types are contaminating the food chain and affecting soil and human health. Pre-treatment at the source point reduces the pollution load into natural bodies and allows for traditional and modern technology to be used to rehabilitate the polluted field. Importance of increasing farmer awareness for safe use of industrial waste, effluent and sewage during agricultural production is realized in this regard. Before cultivating food crops, organic and inorganic soil additives should be used to remediate contaminated soils and biochar seems to offer possible solution.